Empowering Public Freight Drivers through Improving Vehicle Emergency Response Capabilities - Widjajanti, Endang (Green Publisher Indonesia, 2024)
The evaluation was carried out to determine the skills of emergency response handling by public freight drivers to vehicle damage so that it can be used to improve the ability of public freight drivers to anticipate emergency response. Location of survey survey is in Jakarta and surrounding areas. The sampling technique used in this study is non probability sampling and Purposive Sampling. The study results showed that more than 50% of public freight drivers do all tasks of delivering goods such as driving, cleaning vehicles, maintaining vehicles, supervising the process of loading/unloading and maintaining cargo. The most common types of vehicle damage experienced by public freight drivers are broken tires, transmission system disturbances and brake system disturbances. Public freight drivers tend to repair damage from broken tires, transmission system disturbances, brake system disturbances themselves, whereas to repair damaged axles and engine damage, drivers tend to contact the nearest repair shop and/or contact the company. The evaluation results show the need to improve the driver's ability in emergency response related to vehicle conditions such as inspection of vehicle equipment, vehicle loading procedures, tire burst, transmission system disturbances, brake system disturbances.